The girls of Mischief Bay [large type] - Mallery, Susan (Mallery, Susan. Mischief Bay., 2015)
"Nicole Lord wants to be a good wife, but there's a difference between being supportive and supporting her husband. He quit his job to write a screenplay she's never seen, leaving Nicole to run the house, work full-time, and care for their young son. Can she say enough is enough without losing the man she loves? Sacrificing a personal life for her career is how Shannon Rigg became V.P. at her firm, but she wonders whether she made the right choice. An exciting new love convinces her it's not too late--until he drops a bombshell that has her questioning whether she can have it all. Although Pam Eiland adores her husband, she feels restless now that the kids are grown. Finding sexy new ways to surprise her man brings the heat and humor back to their marriage, but when unexpected change turns her life upside down, she'll have to redefine herself. Again. Through romance and heartbreak, laughter and tears, the girls of Mischief Bay will discover that life is richer with friends at your side" -- from author's web site.